If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2c(3b + -4) + -3b(-5 + 2c) = 0 Reorder the terms: 2c(-4 + 3b) + -3b(-5 + 2c) = 0 (-4 * 2c + 3b * 2c) + -3b(-5 + 2c) = 0 Reorder the terms: (6bc + -8c) + -3b(-5 + 2c) = 0 (6bc + -8c) + -3b(-5 + 2c) = 0 6bc + -8c + (-5 * -3b + 2c * -3b) = 0 6bc + -8c + (15b + -6bc) = 0 Reorder the terms: 15b + 6bc + -6bc + -8c = 0 Combine like terms: 6bc + -6bc = 0 15b + 0 + -8c = 0 15b + -8c = 0 Solving 15b + -8c = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '8c' to each side of the equation. 15b + -8c + 8c = 0 + 8c Combine like terms: -8c + 8c = 0 15b + 0 = 0 + 8c 15b = 0 + 8c Remove the zero: 15b = 8c Divide each side by '15'. b = 0.5333333333c Simplifying b = 0.5333333333c
| 6w^2+11w+3=0 | | 10-10x=1333-31x | | 1/4x2/4 | | 2k^2-7k-15=0 | | 5x+3=4x-4 | | z^2-z+5=0 | | 4(2-4x)=16 | | 3x=22x | | 3ix-5+3i=(3-1)y+1 | | 7m-2m= | | 53-2x=25x+20 | | 6x+129=16x-11 | | 8-10=2x | | 4u^2+23u+28=0 | | 10x+2=8x+14 | | -2x+4=-4x+2 | | (2x^2y-3y^4)dx+(3x^3+2xy^3)dy=0 | | (2x^2y-3y^4)dx+(3x^3-2xy^3)dy=0 | | 4x+2=-2x+7 | | -3x+7=4x-12 | | (13-6)*(2+5)= | | 45+105+(4x-15)+5x=360 | | 5x+5=2x+9 | | 24=4(2-2x) | | 10x-8=8x+7 | | 4y+12=2y-10 | | 6(7x+1)=43x | | 7x-7=3x+10 | | x^2-((2/3)*x)-(27/16) | | x^2-(2/3x)-(27/16)=0 | | 4U^2-19u+15=0 | | 5x-37=7x+47 |